DESENVOLVIMENTO DE METODOLOGIAS ELETROANALÍTICAS PARA O MONITORAMENTO DE FÁRMACOS EM URINA E ESTRUVITA USADAS COMO FERTILIZANTE NA AGRICULTURA ORGÂNICA - Silva, Luiz Ricardo Guterres e (2020)
Organic agriculture has been gaining prominence year after year, as it is a cultivation modality that uses natural fertilizers, to ensure the quality of food and promote sustainability. Among the natural fertilizers, we can highlight struvite (MgNH4PO4·6H